The study of relationship between effect of some environmental condition in some physiological haematological in cross bread Holstein Friesian Dairy: H.Y.Al-Baiti, M.A.Al-Zahiri ,A.M.Al-Kinani - Al-Baiti, H. Y. (The Iraqi Journal of Veterinary Medicine, 2010)
The aim of this study was to conduct the effect of environmental conditions(temperature degree and relative humidity) for three seasons ( winter , springand summer) on some physiological, productive and functional parameters ofFriesain dairy cow and their relation with two different lactational stages (Second and third lactational stages). This study was carried out in Al-TathaminDairy plan, Al-Dijyla’a ( Iraqi – Jordan Company) at Waist province. Thirtydairy cows were selected and divided in two groups, each group contains fifteencows depended on lactation stage. Blood sample were collected at monthlyintervals for hematological examination viz; packed cell volume haemoglobin,milk yield and milk traits such as fat percentage, total solid material, and nonfattysolid material was measured. The period of study lasted from 1-January2006 up to 1-september 2006. The result revealed following:1. Significant decreased in the haemoglobin concentration and packed cellvolume were decreased in the two lactation stages (second and thirdlactation stage).2. Milk yield was non significant decreased during summer as a result inincreased environmental temperature about 14.1co to 36.1co and decreaserelative humidity about 62.2% to 20%.3. Milk percentage decrease and reach it’s minimum level during summer forthe third lactation stage to reach 2.6%.4. Total solid and total solid non-fatty material of milk percentage increased forthe two lactation stages during spring to reach (12.59%, 9.3%) fore the thirdlactation stage and (12.22%, 9.6%) fore the second lactation stage.